Polidocanol foam sclerotherapy of persisting postoperative seromas after varicose vein surgery: a series of six cases. (October 2013) - Moritz, R K C; Reich-Schupke, S; Altmeyer, P; StüCker, M
Objective: The aim of our case series was to show the therapeutic effect andthe safety of the use of polidocanol foam in ultrasound-guided sclerotherapy treatment ofrelatively small postoperative seromas after varicose vein surgery. Methods: We treated six patients with postoperative seromas after varicose vein surgery that were refractory to conventional treatments including compression dressings, repeated needle aspirations and manual lymph drainage. Results: A complete regression of the fluid collections was seen after one and two ultrasound-guided injections of polidocanol foam into the seroma cavity in two cases, respectively. Up to five treatment sessions and up to four further needle aspirations were necessary for the remaining two patients until complete regression of the seromas. No side-effects were reported. Conclusion: This is the first case series to report of the regression of postoperative seromas after varicose vein surgery induced by polidocanol foam sclerotherapy.